Fintech seen through a sustainability lens: Transformative potential and actual achievements - Paulet, Elisabeth; Relano, Francesc (Management international / International Management / Gestiòn Internacional, 2023)
This paper expands traditional approaches on the impact of Fintech in the financial landscape. Beyond the perspective of technological and market-driven innovations, our study explores the role of Fintech companies in the domain of sustainability. The empirical analysis is based on a sample composed of traditional banks, so-called ethical banks, and various types of Fintech in Switzerland. The results show that, in the domain of sustainability, Fintech companies are far less game-changing than commonly thought.